Brimstone and Treacle: Charles Spurgeon’s Humor in the Teaching of Preaching (Homiletic, 2015)
While Charles Spurgeon’s use of humor in his preaching has been well-documented, his use of wit in the teaching of preaching to students at his Pastor’s College in London has been largely ignored. This article surveys his lighthearted approach to the teaching of preaching technique as seen in humorous anecdotes, sarcastic descriptions, and amusing illustrations. It concludes with a brief admonition for modern preaching textbook authors to follow Spurgeon’s lead in the use of humor in their work.